2010
DOI: 10.1002/jsfa.3976
|View full text |Cite
|
Sign up to set email alerts
|

Changes in volatile aroma compounds of organic fragrant rice during storage under different conditions

Abstract: A greater extent and higher rate of undesirable changes in volatile compounds were found in samples stored under Nylon/LLDPE/ambient temperature condition. Nevertheless, this condition is acceptable for the retail trade of organic rice in Thailand. Storage conditions using reduced temperature or better packaging materials may be more appropriate for exported rice or superior-grade fragrant rice to better maintain the desirable rice aroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 25 publications
5
31
0
Order By: Relevance
“…Packaging pouches used in this study were purchased from Janjaras Chem Supply Co., Ltd., Bangkok., Thailand. Detailed characteristics of the OPP/Al/LLDPE and Nylon/LLDPE pouches were reported elsewhere (Tananuwong & Lertsiri, 2010). Briefly, an opaque OPP/Al/LLDPE pouch, with excellent light protection, had lower water and oxygen vapour permeability than had a transparent Nylon/LLDPE pouch.…”
Section: Methodsmentioning
confidence: 99%
“…Packaging pouches used in this study were purchased from Janjaras Chem Supply Co., Ltd., Bangkok., Thailand. Detailed characteristics of the OPP/Al/LLDPE and Nylon/LLDPE pouches were reported elsewhere (Tananuwong & Lertsiri, 2010). Briefly, an opaque OPP/Al/LLDPE pouch, with excellent light protection, had lower water and oxygen vapour permeability than had a transparent Nylon/LLDPE pouch.…”
Section: Methodsmentioning
confidence: 99%
“…() showed that as storage time increased, the concentrations of the key aroma compound, 2‐AP decreased whereas the off‐flavor compounds, n ‐hexanal and 2‐pentylfuran increased in aromatic rice. Tananuwong and Lertsiri () found an increase in hexanal, 2‐pentylfuran, 1‐octanol, and 4‐vinyl guaiacol but decreases in 2‐AP and geranyl acetone for organic rice after two months storage. Suzuki et al.…”
Section: Effects Of Storage On Rice Grain Qualitymentioning
confidence: 99%
“…The maximum 2AP concentration is varietydependent (Guofo et al 2010) and occurs four or five weeks after heading (WAH) and decreases to 20% of maximum at seven or eight WAH (Itani et al 2004). Furthermore, 2AP concentration decreases with storage time and temperature (Tananuwong and Lertsiri 2010). Consequently, even rice of the same variety grown under the same conditions may show a significant difference in 2AP concentration due to differences in harvest date and postharvest handling.…”
mentioning
confidence: 99%